Soil stabilisation using novel binders - Ng, Charlene Wei Xuan (Nanyang Technological University, 2024)
This study responds to the pressing challenges faced by Singapore, a land-scarce city-state witnessing a surge in solid waste, primarily from excavated marine clay (MC) and incinerated bottom ash (IBA). Amidst escalating urbanization and population growth, innovative waste management solutions are imperative. This research focuses on the development of a sustainable pumpable mixture for land reclamation, evaluating alternative treatments for MC and IBA while emphasizing the environmental drawbacks of ordinary Portland cement (OPC) in comparison to ground granulated blast-furnace slag (GGBS) for treating IBA-MC. The study employs a comprehensive approach, utilizing flow value assessments, pH evaluations, bulk density, water content, dry density and unconfined compression strength (UCS) tests to comprehensively understand the properties of the treated materials. IBA proves transformative in modifying the mixture's characteristics, and GGBS displays potential in mitigating water content, enhancing bulk and dry density, and elevating UCS values, crucial for creating an environmentally sustainable pumpable mixture suitable for land reclamation. However, additional study is required to enhance the strength of GGBS treated IBA-MC. Crucially, a comparative analysis reveals that OPC treated IBA-MC exhibits higher unconfined compression strength GGBS treated IBA-MC however the environmental impact of OPC production produces with significant carbon emissions and energy consumption in contrast to GGBS. The study underscores the sustainability benefits of using GGBS activated with IBA as a more environmentally friendly alternative, contributing to reduced carbon footprints and lower energy consumption in the creation of the pumpable mixture. This research thus not only addresses the intricate challenges of waste management and land scarcity in Singapore but also advocates for the adoption of sustainable alternatives, aligning with global efforts to minimize the ecological impact of construction materials.